Unintended Consequences: Unknowable and Unavoidable, or Knowable and Unforgivable? - Suckling, James; Hoolohan, Claire; Soutar, Iain; Druckman, Angela (Frontiers in Climate, 2021)
Recognizing that there are multiple environmental limits within which humanity can safely operate, it is essential that potential negative outcomes of seemingly positive actions are accounted for. This alertness to unintended consequences underscores the importance of so called ‘nexus’ research, which recognizes the integrated and interactive nature of water, energy and food systems, and aims to understand the broader implications of developments in any one of these systems. This article presents a novel framework for categorizing such detrimental unintended consequences, based upon how much is known about the system in question and the scope for avoiding any such unintended consequences. The framework comprises four categories (Knowable and Avoidable; Knowable and Unavoidable; Unknowable and Avoidable, and Unknowable and Unavoidable). The categories are explored with reference to examples in both the water-energy-food nexus and planetary boundary frameworks. The examples highlight the potential for the unexpected to happen and explore dynamic nature of the situations that give rise to the unexpected. The article concludes with guidance on how the framework can be used to increase confidence that best efforts have been made to navigate our way towards secure and sustainable water, energy and food systems, avoiding and/or managing unintended consequences along the way.